Penerapan Game Interaktif Aplikasi Kahoot untuk Meningkatkan Minat Belajar Matematika Siswa - Efendi, Annisa Mulya; Yudhi, Prima; Ergusni, Ergusni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Effective learning is student-centered learning. This is because students are the center of learning. Student involvement in learning is of course very meaningful to provide experience for students. Some efforts to involve students in learning are using learning media. Appropriate learning media must be adapted to the needs of students in the class. The learning carried out at SMK N 1 Batipuh is based on the results of needs and material analysis that students show more enthusiasm for learning when using media. One of the right media is the interactive game application kahoot which means that the media can be accessed easily by students. The kahoot application interactive game can increase student interest in learning because it is multimedia in nature and is a